DOMINANT FACTORS OF WORK-LIFE BALANCE IN WOMEN ENTREPRENEURSHIP IN HOME-BASED FOOD BUSINESS: AN EMPIRICAL STUDY FROM BANGLADESH PERSPECTIVE - Oridi, Faria Islam; Khanam, Mushfika; Khatun, Akhi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Purpose: The study aims to identify the factors influencing women entrepreneurs to balance their work and life while performing home-based business in Bangladesh. Methodology: A qualitative approach is adopted in this study. Both snowball and convenience sampling techniques are used to get the study participants. Using a semi-structured questionnaire, the researchers conducted 20 in-depth face-to-face interviews of women entrepreneurs from four districts including kushtia, jhenaidah, jashore, and khulna. Content analysis approach is applied to analyze data. Findings: The results of this study demonstrate that the main elements influencing the work-life balance of women entrepreneurs include multiple tasks, time management, social and family support, mental and physical health issues, dependent care, financial and socio-cultural factors. Furthermore, the study discovers that most of the respondent experience challenges in balancing their personal and professional lives. These challenges differ depending on demographic characteristics. Women entrepreneurs, who have supportive families, can reduce family conflicts related to business operations from home. The study also reveals that home-based food business creates the opportunity for women entrepreneurs to keep their family as the first priority. Practical Implications: The results will be useful in developing an all-encompassing framework to support women entrepreneurship in home-based food business. It will encourage women to start their business to achieve financial ability as well as personal fulfillment. The academicians can further scrutinize the dimensions of work-life balance to develop suitable balancing strategies for home-based women entrepreneurs. Moreover, the study findings will generate fundamental guidelines for policymakers in promoting entrepreneurial endeavors among women in home-based business.